ANALISIS KARAKTERISTIK MASYARAKAT YANG TERLIBAT DALAM KEGIATAN REHABILITASI DAS DAN BIAYA PEMBUATAN TAHUN PERTAMA (P0), PEMELIHARAAN TAHUN PERTAMA (P1) DAN PEMELIHARAAN TAHUN KEDUA (P2) REHABILITASI DAS SWARANGAN - Fadeliansyah, Fadeliansyah; Kadir, Syarifuddin; Istikowati, Wiwin Tyas (Jurnal Hutan Tropis, 2024)
Implementation of watershed rehabilitation activities requires technical design, namely short-term detailed planning which becomes a reference for implementation in the field, both physical and non-physical activities carried out during the creation of the first year (P0), maintenance of the first year (P1) and maintenance of the second year ( P2). This research was carried out at PT. Pro Sarana Cipta Tambang Kandangan which was carried out in Swarangan Village Pelaihari Wildlife Reserve which is managed by the South Kalimantan Natural Resources Conservation Center, Jorong District, Tanah Laut Regency, South Kalimantan Province for three months from October 2023 to January 2024. The method used in this research is purposive sampling, calculated from the results of the questionnaire, recommended from the results of interviews in the field. The results of the research are the total cost requirements carried out by PT. Pro Sarana Cipta during planting activities (P0) amounted to Rp. 1,411,753,200, during first year plant maintenance (P1) amounted to Rp. 691,792,200,- and second year plant maintenance costs (P2) amounted to Rp. 559,822,000,- so The total total costs reached IDR 2,663,367,400.-.